Contact Tracing and Awareness-Raising Measures for Travelers Arriving in Thailand from High Risk Areas of Coronavirus Disease (COVID-19): A Cluster of Imported COVID-19 Cases from Italy, March 2020 - Wongsanuphat, Suphanat; Jitpeera, Charuttaporn; Konglapamnuay, Duangjai; Nilphat, Chuthawan; Jantaramanee, Supiya; Suphanchaimat, Rapeepong (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2020)
Coronavirus Disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Since before a global pandemic was declared by the World Health Organization, many countries have been implementing stringent screening protocols on international travelers. In Thailand, a ‘Health Beware Card’ (HBC) was provided to all travelers at ports of entry. On 5 Mar 2020, the Department of Disease Control (DDC) of the Thai Ministry of Public Health received a notification that there was a COVID-19 confirmed case who traveled from Lombardy, Italy. A joint investigation team commenced an investigation to describe epidemiological characteristics, and identify contacts and possible source cases. Totally three confirmed cases of COVID-19 and one asymptomatic infection were identified in this investigation. The index case was a 41-year-old Thai male. He notified local health providers immediately after the onset of symptoms as per HBC recommendations. Contact tracing led to the identification of three additional cases: two were peers who traveled together with the index case to Italy and one was a close friend. The attack rate among people visiting Italy in this cluster was 50%. Contact tracing was a key control measure to stop the spread of COVID-19, and awareness-raising measures limited local transmission from imported cases. For people traveling from a disease-infected zone, mandatory quarantine and laboratory screening must be enforced.